Lysophosphatidic Acid Is an Inflammatory Lipid Exploited by Cancers for Immune Evasion via Mechanisms Similar and Distinct From CTLA-4 and PD-1 - Mathew, Divij; Torres, Raul M. (Frontiers in Immunology, 2021)
Immunological tolerance has evolved to curtail immune responses against self-antigens and prevents autoimmunity (1). One mechanism that contributes to immunological tolerance is the expression of inhibitory receptors by lymphocytes that signal to dampen immune responses during the course of an infection and to prevent immune-mediated collateral damage to the host (2). The understanding that tumors exploit these physiological mechanisms to avoid elimination has led to remarkable, but limited, success in the treatment of cancer through the use of biologics that interfere with the ability of cancers to suppress immune function. This therapy, based on the understanding of how T lymphocytes are normally activated and suppressed, has led to the development of therapeutic blocking antibodies, referred to as immune checkpoint blockade, which either directly or indirectly promote the activation of CD8 T cells to eradicate cancer. Here, we highlight the distinct signaling mechanisms, timing and location of inhibition used by the CTLA-4 and PD-1 inhibitory receptors compared to a novel inhibitory signaling axis comprised of the bioactive lipid, lysophosphatidic acid (LPA), signaling via the LPA5 receptor expressed by CD8 T cells. Importantly, abundant evidence indicates that an LPA-LPA5 signaling axis is also exploited by diverse cancers to suppress T cell activation and function. Clearly, a thorough molecular and biochemical understanding of how diverse T cell inhibitory receptors signal to suppress T cell antigen receptor signaling and function will be important to inform the choice of which complimentary checkpoint blockade modalities might be used for a given cancer.